The Influence of the UV Light on the PVC Sheets Adopted with Some Aromatic Amines - Abdullah, Salah M.; F. Alwan, Aseel; M. Majeed , Atheer (Al-Nahrain Journal of Science, 2022)
Adopted PVC with aromatic amines, (dimethyl amino benzyldehyde (No.1), aminophenol (No.2), benzidine (No.3) and 4,4-diaminodiphenylsulphone (No.4) were investigated using UV light source at 340 nm. the changing in FTIR spectroscopy for carbonyl and polyene groups was monitored, I(C=C) and I(c=o) was calculated during different period of irradiation time, in addition, the molecular weight of PVC and PVC adopted sheets was obtained using viscosity method. the results show the aromatic amines behave as a good photostabilizer in order: No. No.2No.3 > No.4. The morphology of the sheets surface achieved by AFM analysis which assigned that the roughness factor (Rq) of the blank, No.2 and No.4 sheets was (Rq=73.0), (Rq=240), (Rq=213) before irradiation and (Rq=180), (Rq=281), (Rq=285) after radiation respectively.